Morphogenesis and migration: investigating the roles of Rap1 in epithelial cell behaviors during Drosophila oogenesis - Messer, Christopher Luke Bernard (Kansas State University, 2023)
Epithelia line many of the body’s surfaces and organs where they perform essential functions like nutrient absorption and wound healing. Epithelia are consistently challenged during development and as a part of normal tissue homeostasis. Moreover, most cancers originate in epithelia. Normal developmental apoptosis, cell division, and cell rearrangements test epithelial integrity and cell-cell adhesions. How epithelial cells maintain cell-to-cell adhesions and tissue integrity despite challenges imposed by the tissue environment is poorly understood. The small GTPase Rap1 has roles in cell polarity, cell-cell adhesion, and cell migration. In this dissertation I use the Drosophila ovary to investigate how Rap1 contributes to epithelial integrity and cell migration. Drosophila oogenesis provides a robust, genetically accessible model to study Rap1 function in epithelia. First, I utilize the Drosophila ovariole, a string of progressively developing egg chambers within the ovary, to understand how Rap1 contributes to epithelial integrity in a growing tissue. As oogenesis progresses, egg chambers elongate, which presents a challenge to the overlying follicular epithelium. I found that Rap1 was required to maintain tissue and cell shapes and promote cell viability during tissue elongation. Egg chambers deficient for Rap1 had distorted tissue shapes, stretched individual cells, and failed enrichment of the homophilic cell-cell adhesion protein E-Cadherin. Moreover, Rap1 deficient egg chambers lost follicle cells via apoptosis as indicated by an increase in caspase activity. These results support dual functions for Rap1 in promoting normal epithelial integrity and cell viability during tissue growth of the ovary. While Rap1 has numerous roles in development and disease, signaling partners that facilitate Rap1 function remain unclear. Therefore, I next used the Drosophila border cell model of collective cell migration to screen for potential Rap1 effectors required for migration. Border cell migration is a powerful in vivo model of collective cell migration. A group of four to six migratory border cells, along with the central pair of organizing polar cells, migrate across the egg chamber to reach the oocyte. Border cells maintain adhesions to one another and overall cluster polarity. Properly regulated Rap1 activity is essential for efficient migration. I used the strong border cell migration defects reported for constitutively active Rap1, Rap1[superscript V12], to screen for X-chromosome deficiency regions that partially restored migration to the oocyte. I identified seven X-chromosome deficiencies that restored migration to Rap1[superscript V12] expressing border cells. Furthermore, I mapped three of these regions to single genes, and report fz4, Usp16-45, and sno as candidate Rap1 interacting genes in border cell migration. Taken together these results demonstrate a requirement for Rap1 in epithelial integrity and cell viability during oogenesis and identify three candidate effectors that facilitate border cell migration. Results from this study are broadly relevant, as epithelial morphogenesis and collective cell migration are highly conserved features of metazoan development.
Keywords: Rap1 GTPase; Collective migration; Epithelial integrity; Cell viability; Oogenesis